PEMBERDAYAAN EKONOMI PEREMPUAN : STRATEGI PENENTUAN HARGA POKOK PRODUKSI DAN STRATEGI PROMOSI PADA INDUSTRI RUMAHAN - Laras Pratiwi; Yeni Fitriani Somantri; Suci Putri Lestari (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
The development of micro-scale industries is able to provide a significant increase in the economic resilience of the community, but in fact it is not yet fully integrated with the micro-scale home industry players. This community service activity was held with the aim of empowering the economy of women, especially in the business sector of the Al-Mahabbah Foundation, Cimahi City, with the Khusi Cookies product brand. This activity is carried out into three stages, namely the planning stage, the business simulation stage and the evaluation stage. This activity is able to provide benefits for Khusi Cookies business players in the form of creating knowledge about calculating the cost of production and opening a mindset of expanding promotional strategies through social media.. (Times New Roman 10, 1 space, 1 paragraf).